Predictors of Weight Bias in Exercise Science Students and Fitness Professionals: A Scoping Review - Lara Zaroubi; Tiffany Samaan; Angela S. Alberga (Hindawi Limited, 2021)
Background. Although previous studies have reported weight bias among students and professionals in exercise science, physical education, kinesiology, and fitness instruction, predictors of weight bias in these professions have not been extensively reviewed. Aim. The purpose of this scoping review was to explore the available literature on predictors of weight bias in exercise science students and fitness professionals to identify key concepts and research gaps. Methods. PubMed and ERIC were searched from January 1990 to May 2019. Eighteen studies were included in this review. A thematic analysis was conducted. Findings. Six main themes were drawn from these studies including beliefs in the personal controllability of weight; sex differences; enrollment in a health sciences-related program; psychosocial and personal factors; knowledge of obesity; lack of personal history, family, or friend with obesity. Our scoping review highlighted diverse predictors of weight bias among exercise science students and professionals that warrant further study and intervention.